2018
DOI: 10.1371/journal.pgen.1007211
|View full text |Cite
|
Sign up to set email alerts
|

Th-POK regulates mammary gland lactation through mTOR-SREBP pathway

Abstract: The Th-inducing POK (Th-POK, also known as ZBTB7B or cKrox) transcription factor is a key regulator of lineage commitment of immature T cell precursors. It is yet unclear the physiological functions of Th-POK besides helper T cell differentiation. Here we show that Th-POK is restrictedly expressed in the luminal epithelial cells in the mammary glands that is upregulated at late pregnancy and lactation. Lineage restrictedly expressed Th-POK exerts distinct biological functions in the mammary epithelial cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…I-WAT and E-WAT were washed with PBS, cut into small pieces, and digested with 1 mg/mL Collagenase (Worthington, Lakewood, New Jersey) at 37°C for 60 minutes. SVF cell culture, FACS analyses, and adipogenic induction were performed as described [ 40 , 41 ]. For PDGF and VP treatment experiments, SVF cells were treated with PDGF or VP for 4 days before FACS analyses and adipogenic induction.…”
Section: Methodsmentioning
confidence: 99%
“…I-WAT and E-WAT were washed with PBS, cut into small pieces, and digested with 1 mg/mL Collagenase (Worthington, Lakewood, New Jersey) at 37°C for 60 minutes. SVF cell culture, FACS analyses, and adipogenic induction were performed as described [ 40 , 41 ]. For PDGF and VP treatment experiments, SVF cells were treated with PDGF or VP for 4 days before FACS analyses and adipogenic induction.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that mammary epithelial cells (MECs) play key roles in milk protein and lipid biosynthesis [ 1 3 ]. During lactation, MECs secrete large quantities of milk proteins, notably caseins.…”
Section: Introductionmentioning
confidence: 99%
“…Automated scoring and quantitative evaluation of DAB stained IHC images are performed using open source IHC Profiler Plugin 66 in ImageJ software. H-score was calculated by adding the percentage of high positive (×3), positive (×2), and low positive cells (×1) as described 67 . Hscore has a possible range of 0-300.…”
Section: Histological and Immunohistochemical Stainingmentioning
confidence: 99%